Model szacowania pracochłonności pozyskiwania drewna w drzewostanach ze śniegołomami - Szewczyk, Grzegorz; Stańczykiewicz, Arkadiusz (Leśne Prace Badawcze, 2012)
The study makes a comparative analysis of labour use during timber harvesting with winches attached to agricultural tractors in undamaged stands and in snowbreak stands. Initially a model was used to determine the indicators of increased labour needed for stand maintenance following disturbance of the stand compared to a planned harvest. The model included the dependence of timber harvesting labour use on cut intensity and the length of each period of work during the typical working day in the undamaged stands, both in undamaged stands, and in snowbreak stands, a large proportion of working time was spent loading the vehicle and driving during loading of the vehicle. The average time period spent driving timber in both stand types was similar, but they differed in the allocation of labour. In undamaged stands most time was dedicated to use of agricultural tractors to harvest timber, whereas in damaged stands most time went on loading timber. Estimates of work consumption in snowbreak stands can consequently be measured in the same way as standard cultivated stands, however values should be increased by 227% in snowbreak stands to compensate for the differences in the load formation time.